3t-4s+1-t=

Simple and best practice solution for 3t-4s+1-t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-4s+1-t= equation:


Simplifying
3t + -4s + 1 + -1t = 0

Reorder the terms:
1 + -4s + 3t + -1t = 0

Combine like terms: 3t + -1t = 2t
1 + -4s + 2t = 0

Solving
1 + -4s + 2t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -4s + -1 + 2t = 0 + -1

Reorder the terms:
1 + -1 + -4s + 2t = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -4s + 2t = 0 + -1
-4s + 2t = 0 + -1

Combine like terms: 0 + -1 = -1
-4s + 2t = -1

Add '-2t' to each side of the equation.
-4s + 2t + -2t = -1 + -2t

Combine like terms: 2t + -2t = 0
-4s + 0 = -1 + -2t
-4s = -1 + -2t

Divide each side by '-4'.
s = 0.25 + 0.5t

Simplifying
s = 0.25 + 0.5t

See similar equations:

| -81=t+-5 | | z-24=31 | | 2w+-3=7 | | b+66=-25 | | -19.24=g+-1 | | 10x^2/10=0 | | 3y+Y+5=21 | | Y-6=2(x-9) | | 10x^2/10=b | | 16x+4y=340 | | 4(8-x)+1=13 | | t+-218=376 | | (3i)(6i)= | | -9d=783 | | 4x+10+3x-5+x-5=180 | | b+-585=9 | | 80+4x-140=180 | | m-25=-8 | | 1.5x+13=2.4+4 | | 8+3z=17 | | log14/x=2 | | 2/3x-5/6x=1 | | (15m2)1/3 | | 45=r-14 | | log8/x=2 | | 5-2k=3 | | 8a+2b-5c+10= | | 6x-16=3x-54 | | n/4=86/344 | | 2p=70 | | X-5+3x-5+4x+10=180 | | -u=61 |

Equations solver categories